Management of Improving Household Economic Structure to Overcome Stunting - Kamuri, Klaasvakumok J.; Aman, Dominikus Kopong T.; Neno, Marianus S.; Manongga, Irience R.A.; Nenohai, Marylin E.S. (Interdisciplinary Social Studies, 2023)
Background: The increase in stunting continues to occur in this world, including in Indonesia. the need for the cooperation of various interests to reduce stunting interventions. Various studies have shown that stunting is a lack of nutrition caused by a low household economic structure. Aim: This study aims to determine the management of improving household economic structure as an effort to overcome stunting with case studies conducted on stunted households in Kupang Regency, TTS Regency, and Manggarai Regency. Method: This study uses a qualitative method. Data obtained through documentation techniques. Findings: The results of this study indicate that the management of increasing the household economic structure must be carried out jointly and cannot be carried out by only one sector. Based on several studies, the cause of stunting is a lack of nutrition. Malnutrition is caused by a lack of household welfare, and household economic welfare is caused by low education. So that the main source is education which is still low. Thus, the management of improving the household economic structure needs to start with improving education in Kupang, TTS, and Manggarai districts.